Injuries at the Work Place: An Examination of the Basis for Claim Under Nigeria’s Employees Compensation Act (ECA) 2010 (British Journal of Multidisciplinary and Advanced Studies, 2024)
The Employer employee relationship has been in existence since the time immemorial, Master servant relationship was initially practiced up to the time where such relationship was abolished, which was replaced with an institutionalized relation i.e. Employer employee relations, where each of the parties has his own rights and duties spelt out by the Laws establishing and guiding their relationship. In most cases during the course of this relationship, parties may sustain an injury of different degrees, ranging from partial or permanent disabilities, at some instances to the extent of even loss of life in the course of that employment, depending on the nature of the employment. This work will explore the available statutes ranging from the International treaties which Nigeria happened to be a signatory to, and the other Nigerian legislations, and Case Laws regulating the Employee employer relationship with a view to examining  such injuries based on their compensability and what will qualify them to be so i.e. the basis for the claim of damages based on the injuries sustained under the Employee’s Compensation Act 2010, and also to examine how such claims could be made appropriately in accordance with the law.  At the end of this work, the Employer and employee would be better educated in the nature of the injuries that attracts compensation as well as what qualified them to be so, and how it could be done in accordance with the law